The Roles of Islamic Education in Building Students’ Character within Indonesia Public Schools - Darlan Darlan; Sagaf S. Pettalongi; Rustina Rustina (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2021)
This study examined the role of Islamic education in building students’ character within Indonesia public schools. In conducting the study, we used a qualitative case study method. The case of this study was a state senior high school in Palu city. Data were gathered through direct field observation, in-depth interviews which involve teachers and students. We also analyzed written material, such as the school curriculum, to understand how the character building strategies were integrated in the curriculum. Iur study found that teachers implement character building strategies through several stages, namely the stages of planning, the stages of learning implementation, and the stages of evaluating Islamic religious education learning. The characters values were embedded in the learning of Islamic religious education. This included the integration of character values in the school curriculum and they were taught in every day classroom leanings and in extracurricular activities.